2013
DOI: 10.1038/nsmb.2736
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of distinct substrate-recruitment pathways in the yeast exosome by EM

Abstract: The eukaryotic exosome is a multi-subunit complex typically composed of a catalytically inactive core and the Rrp44 protein, which contains 3’ to 5’ exo- and endo-ribonuclease activities. RNA substrates have been shown to be recruited through the core to reach Rrp44's exoribonuclease (EXO) site. Using single particle electron microscopy and biochemical analysis, we provide visual evidence that two distinct substrate recruitment pathways exist. In the through-core route, channeling of the single stranded substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 44 publications
7
95
0
Order By: Relevance
“…Both complexes were mono-disperse under EM and hence were suitable for single-particle two-dimensional (2D) classification analysis. As expected, the 2D class averages of the Exo10 complex showed classical Exo10 structures, as previously observed [13,17]. In contrast, the 2D class averages of the Exo10-Ski7 complex revealed a prominent additional density attached to the top of the Exo10 core ( Figure 1C).…”
Section: Purification Of the Endogenous Exo10-ski7 Complexsupporting
confidence: 52%
See 3 more Smart Citations
“…Both complexes were mono-disperse under EM and hence were suitable for single-particle two-dimensional (2D) classification analysis. As expected, the 2D class averages of the Exo10 complex showed classical Exo10 structures, as previously observed [13,17]. In contrast, the 2D class averages of the Exo10-Ski7 complex revealed a prominent additional density attached to the top of the Exo10 core ( Figure 1C).…”
Section: Purification Of the Endogenous Exo10-ski7 Complexsupporting
confidence: 52%
“…The solvent exposure of the Rrp44 active site in the apo structure of Exo10 also suggests another pathway where RNA substrates reach the Rrp44 active site without passing through the central channel of the core. This direct-access pathway does not require RNA substrates to have very long single-stranded 3′ overhangs and enables Exo10 to process RNAs with a tertiary structure [17]. Interestingly, our previous structural studies have indicated that Exo10 adopts distinct conformations in the through-core and direct-access pathways, of which the latter is very similar to the apostate of the complex [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus different temperatures, solution conditions, and biochemical reaction time-points will yield thermodynamics and kinetics information for bio-macromolecule complexes correlated with structural information. Overall, these data lead to a deeper insight into molecular mechanisms [13,14].…”
Section: Inhomogeneous Samplesmentioning
confidence: 99%